2015
DOI: 10.11621/pir.2015.0109
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender images in commercials on the self-consciousness of adolescents

Abstract: Television has a strong impact on gender-identity development. Theoretical analysis shows that the direct perception of different gender characteristics in advertising images has a specific impact on gender self-consciousness, primarily at the unconscious level. The purpose of our study was to uncover features of this impact. In this study, the effects of advertising images on the gender self-consciousness of teenagers were investigated. Two hypotheses were examined: (1) Perception of gender images in TV comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was also found that during gender identification, teenage girls tend to place more emphasis on image perception, as they consider it very important to pursue certain images of their ideal role models while forming their own gender identities (Lopukhova, 2015). Special studies of cartoons that feature women revealed the most common methods of depicting women (Ivanova, 2013).…”
mentioning
confidence: 99%
“…It was also found that during gender identification, teenage girls tend to place more emphasis on image perception, as they consider it very important to pursue certain images of their ideal role models while forming their own gender identities (Lopukhova, 2015). Special studies of cartoons that feature women revealed the most common methods of depicting women (Ivanova, 2013).…”
mentioning
confidence: 99%